DIGITAL READING IN EDUCATIONAL CONTEXTS: A PRISMA-GUIDED SYSTEMATIC REVIEW OF MODE EFFECTS, METACOGNITION, AND SOCIAL JUSTICE IMPLICATIONS - Muh. Bahly Basri; Sultan; Usman; Iin Nur Yasinta (LLDIKTI Wilayah X, 2026)
Digital reading has become ubiquitous in educational settings, yet its impact on learning outcomes remains complex and context-dependent. This systematic literature review synthesizes evidence from nine open-access articles published by Taylor & Francis between 2021 and 2025, focusing on digital reading within the education subject area. Adhering to PRISMA 2020 guidelines, the study employed a rigorous screening process to identify relevant research, followed by thematic synthesis to extract key characteristics, outcomes, and implications. The analysis reveals four predominant themes shaping current discourse. First, mode effects highlight inequality-sensitive patterns in large-scale assessments, suggesting that digital formats may exacerbate existing achievement gaps if not carefully managed. Second, metacognitive navigation and strategic processing emerge as critical determinants of comprehension, emphasizing the need for learners to actively regulate their engagement with digital texts. Third, the review examines digital early-literacy ecosystems, underscoring the importance of home literacy supports, shared digital storybook reading, and established quality principles for children’s digital picture books in fostering foundational skills. Fourth, critical–ecological perspectives reframe digital reading through lenses of attention, curriculum design, and social justice, advocating for a holistic approach to future literacy practices. The findings indicate that benefits of digital reading are most pronounced when instructional scaffolds, high-quality design, and equitable access are explicitly prioritized. Conversely, risks such as superficial processing arise when efficiency-driven logics dominate without adequate support for deep comprehension. Consequently, this study proposes targeted implications for pedagogy, interface design, assessment frameworks, and future research directions. By integrating these insights, educators and policymakers can better navigate the challenges of digital literacy, ensuring that technological integration supports rather than hinders equitable and profound learning experiences in diverse educational contexts.